1990
DOI: 10.1136/ard.49.6.349
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia of rheumatoid arthritis: serum erythropoietin concentrations and red cell distribution width in relation to iron status.

Abstract: Immunoreactive serum erythropoietin concentrations were measured in 35 patients with anaemia associated with active rheumatoid arthritis.Based on an evaluation of stainable iron in the bone marrow (marrow iron grade 0-4) and serum ferritin concentrations (concentrations 660 tg/l compatible with iron deficiency) the anaemia was found to be complicated by iron deficiency in 19/35 (54%) of the patients.The mean serum erythropoietin level (57.6 (SD) 27.3) U/I) was sufficiently raised for the degree of anaemia irre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 17 publications
(5 reference statements)
2
20
1
1
Order By: Relevance
“…3,4 Some clinical studies reported a shortened life span for red blood cells in patients with rheumatoid arthritis with the anemia of inflammation, 5,6 but other studies suggest that this is not a consistent finding. 7,8 Finally, defects have been described both in responding to an adequate amount of circulating Epo 9,10 and in producing amounts of Epo appropriate for the severity of the anemia. [11][12][13] Hypoferremia occurs in patients with the anemia of inflammation despite sufficient macrophage iron stores, indicating a block in macrophage iron recycling and return of iron to the serum.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Some clinical studies reported a shortened life span for red blood cells in patients with rheumatoid arthritis with the anemia of inflammation, 5,6 but other studies suggest that this is not a consistent finding. 7,8 Finally, defects have been described both in responding to an adequate amount of circulating Epo 9,10 and in producing amounts of Epo appropriate for the severity of the anemia. [11][12][13] Hypoferremia occurs in patients with the anemia of inflammation despite sufficient macrophage iron stores, indicating a block in macrophage iron recycling and return of iron to the serum.…”
Section: Introductionmentioning
confidence: 99%
“…This confirms the investigations of Morris et al [7] in children with renal anemia (with iron deficiency) who showed an increase in the RDW during oral iron therapy. In contrast to this, Nielsen et al [8] found no difference between iron-repleted and iron-depleted anemic patients with rheumatoid arthritis with respect to the RDW. It follows from the inverse correlation found by us between the baseline hemoglobin and the preoperative change in the RDW that in patients with a low hemoglobin one should first use iron therapy to try to increase the hemoglobin before initiating rhEPO treatment, thus making rhEPO therapy more effective and less costly.…”
Section: Discussionmentioning
confidence: 82%
“…during rhEPO therapy and after bone marrow transplantation [5, 6]. While some authors have already described the diagnostic value of red cell distribution widths as indicators of iron depletion and of the intensity of erythropoietic activity in patients with anemia in rheumatoid arthritis, thalassemia, sickle cell anemia, as well as in alcoholics, malaria patients and patients with iron deficiency anemia there are practically no such studies on the reticulocyte distribution widths [7, 8, 9, 10, 11]. In a double-blind, randomized placebo-controlled trial on HBT avoidance by preoperative rhEPO therapy in cardiac surgery patients without ABD we therefore additionally examined the changes in distribution widths of red cells and reticulocytes during and after therapy with rhEPO (epoetin beta) and considered their diagnostic value in assessing iron status and the kinetics of erythropoiesis.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon could result from the re duction of the renal function previously re ported in elderly patients [29,30]. Another hypothesis to explain the blunted erythropoie tin production in ACD could be the mild degree of anaemia generally observed in ACD, as suggested by Nielsen et al [21], Regarding the erythropoietin production in the ACD related to cancer, no relation was established between erythropoietin and hae moglobin, as shown by Miller et al [9], Ward et al [10], Camacho et al [11] or Joosten et al [4]. However, the inability of the cancer patients to respond to anaemia was not abso lute, since erythropoietin levels were in creased in these patients.…”
Section: Anaemia O F Chronic Disorders In Elderly Patientsmentioning
confidence: 86%
“…iron level <10 gmol/1, C-reactive protein >6 mg/1, orosomucoid >0.9 g/1, haptoglobin >1.4 g/1. in order to distinguish ACD from combined ACD and iron deficiency anaemia (IDA), ferritin levels up to 60 pg/1 associated with transferrin levels less than 2.2 g/1 were chosen, as previous studies had shown that the diagnosis of IDA may not be considered when a cut-off of 60 pg/1 for ferritin levels was chosen [20,21], Blood for hacmatological and biochemical parame ter determinations and for erythropoietin and cytokine assays was obtained at the time of a routine examination.…”
Section: Patientsmentioning
confidence: 99%